Effects of temperature on growth, survival and physiological parameters in juveniles of Lophiosilurus alexandri, a carnivorous neotropical catfish. (24th September 2014) - da Costa, Daniel Pereira; de Oliveira Paes Leme, Fabíola; Takata, Rodrigo; Costa, Deliane Cristina; de Souza e Silva, Walisson; Melillo Filho, Reinaldo; Alves, Gabriela Miccoli; Luz, Ronald Kennedy
Abstract: This study aimed to analyse the effects of different water temperatures on the growth, survival and blood physiological parameters of Lophiosilurus alexandri . Juveniles measuring 12.6 ± 0.5 cm and weighing 30.6 ± 3.6 g were subjected to four water temperature regimes: 23, 26, 29 and 32°C with four replicates. The animals were fed twice daily with formulated diet. The experiment lasted for 35 days. Survival was 100% at all water temperatures, and the best temperature for growth was estimated to be 27.8°C using a quadratic regression model. The estimated temperatures for the best feed conversion and highest feed consumption rates were 26.2 and 28.8°C respectively. The fat visceral‐somatic index was highest at 32°C. The highest haemoglobin and haematocrit values were 29.4 and 32.1°C respectively. For plasma protein and cholesterol, the lowest values estimated were 23.9 and 24.1°C respectively. Glucose and liver nitrogen content increased with rising temperature. Higher values of total ammonia in the water were observed at higher temperatures. No effects of temperature were seen on the amounts of muscle dry matter, nitrogen, energy content and triglycerides or on the hepatosomatic index. Water temperature has an important role in the developmental and blood physiological parameters of juvenile L. alexandri, and the quadratic regression model showed that the appropriate temperature for growth is between 27 and 28°C.